2016
DOI: 10.1111/ane.12669
|View full text |Cite
|
Sign up to set email alerts
|

Effective connectivity in temporal lobe epilepsy with hippocampal sclerosis

Abstract: The limbic networks of TLE patients with and without HS could be different, and the thalamus might play a critical role in TLE patients with HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
(102 reference statements)
0
15
0
1
Order By: Relevance
“…There have been several studies showing involvement of the thalamus in patients with TLE with HS, with potential roles in seizure initiation and propagation [25][26][27]. The hippocampus has important reciprocal connections to the thalamus [28].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies showing involvement of the thalamus in patients with TLE with HS, with potential roles in seizure initiation and propagation [25][26][27]. The hippocampus has important reciprocal connections to the thalamus [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, because most of the patients (81%) with MSA-C also showed some degree of vallecular residue, the difference between the two subtypes does not seem to reflect a pathophysiological difference. This seems to be related to the parkinsonian motor symptoms which could appear in MSA-C [9]. It has been reported that nigrostriatal-dopaminergic denervation is observed in patients with MSA-C, without parkinsonian signs [20].…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of MSA was made by two designated, experienced neurologists according to the guidelines of the 2nd consensus of the Gilman criteria [9]. During each visit to the outpatient clinic, these neurologists asked the patients whether they had been experiencing any dysphagia symptoms, such as difficulty in swallowing, sensory changes in the oral cavity, difficulty in chewing, and aspiration.…”
Section: Methodsmentioning
confidence: 99%
“…speech or visual loss) by demonstrating the anatomical relation between epileptogenic foci and functionally activated areas [7]. Conventional task based (tb) fMRI has the capability of defining regions that are anatomically connected and activated during a given task of interest; whereas resting-state (rs) fMRI maps functional connections with their strength and direction by analyzing the baseline spontaneous fluctuations of blood oxygenation level dependent (BOLD) signals throughout the brain, resulting in several cognitive networks [1,[8][9][10]. Laterality index (LI) is an indirect marker for hemispheric dominancy of language and can be calculated from the data driven with tb-fMRI.…”
Section: Introductionmentioning
confidence: 99%